Pemodelan Direct Quadrate (D-Q) Pada Kendali Kecepatan Motor Induksi Tiga Phasa dengan Field Oriented Control (FOC) Berbasis Kendali P-I - Fauzi, Rizana; Khair, Jumaddil (Fakultas Teknik, Universitas Tadulako, 2018)
The utilization of a 3 phase induction motor is increasingly developing, so research on speed regulation in 3 phase induction motors is also increasingly widely studied. This is because the use of 3 phase induction motors in the industry and especially hybrid vehicles are increasingly being developed. But there are some disadvantages of induction motors, one of which is the characteristics of non-linear parameters, especially rotor resistance which has varying values for different operating conditions, so it cannot maintain its speed constantly if there is a change in load. This, of course, can affect the performance of an induction motor. To get a constant speed and better system performance on load changes a controller is needed. This study aims to model direct-quadrate parameters (D-Q) using the Field Oriented Control (FOC) method based on theÂ Proportional-Integral (PI) controller. With the d-q parameter controlled, the induction motor will be more stable, because the d-q parameter determines the stability of the change in torque and flux in the induction motor. Proportional-Integral (PI) control used is a classic control system that is easy because it does not need to look for a mathematical model of the system, but it remains effective because it has a fairly stable system response, by setting the best combination of proportional (Kp) constants and Integrator constants ( Ki). In the results of the implementation, it can be seen that the use of FOC can be used as an approach in terms of setting the speed of the induction motor, and with the use of the PI control can help the output response get better with a shorter response time to reach the reference value.